(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The effectiveness of any kind of writing comes with powerful narration done by its writer. In this paper i am going to analyse the images and symbols used by Kamala Markandaya in her first novel Nectar in a Sieve, her innate pattern of images and symbols. Deep layer of meanings present in the text is drawn with images and symbols.How effective they are? How much she succeeds in her effort. I am going to take in this paper.